Preliminary study on isozyme variation in silkworm germplasm of bombyx mori (L.) and its implication for conservation - P., Somasondaram; K., Ashok Kumar; K., Thangavelu; P. K., Kar (Universiti Putra Malaysia Press, 2004)
Genetic diversity within and among twelve silkworm Bombyx mori races was investigated using metabolic enzymes viz., a-esterase (a- EST), b-esterase (b-EST), glucose fYphosphate dehydrogenase (G6PD) and acid phosphatase (ACP). A perusal of genetic diversity within and among races indicated that 28% of the observed variation occurred among races and the rest of the variation (72%) within races. The average rate of gene flow between pair wise comparisons of the twelve races was found to be very high (0.62). Genetic relatedness of the twelve races revealed fly the UPGMA dendrogram, showed genetic grouping of races in six clusters. NB4D2 and NB18 are genetically similar while BL-24 and Nistari are genetically distant races. Populations of silkworm races ]-112 and NB4D2 showed the highest genetic diversity, %polymorphism and more alleles, respectively. Their rich genetic diversity needs to be exploited in conservation and breeding programme.